Digital Storytelling in Adult Education: Toward a Conceptual Framework - Marsha Rossiter; Penny A. Garcia (Adult Education Research Conference, 2010)
Interest in digital storytelling in a multitude of settings has burgeoned in recent years. Although digital storytelling is not new in the world of educational technology, so far it has received little attention in the literature of adult learning. Our aim in this paper is to explore elements of a conceptual framework for the use of digital storytelling in adult education.